Worse baseline executive functioning is associated with dropout and poorer response to trauma-focused treatment for veterans with PTSD and comorbid traumatic brain injury. (September 2018) - Crocker, Laura D.; Jurick, Sarah M.; Thomas, Kelsey R.; Keller, Amber V.; Sanderson-Cimino, Mark; Boyd, Briana; Rodgers, Carie; Twamley, Elizabeth W.; Jak, Amy J.
Abstract: Although trauma-focused treatment, including Cognitive Processing Therapy (CPT), effectively reduces PTSD symptoms, treatment dropout, nonresponse, and relapse are substantial. Executive functioning (EF) is essential to engage the cognitive skills involved in CPT (e.g., inhibiting/evaluating distorted thoughts, flexibly generating alternative thoughts). It was hypothesized that worse baseline EF would be associated with reduced CPT completion and responsivity. Seventy-four Iraq/Afghanistan-era Veterans with PTSD and history of mild-to-moderate traumatic brain injury were randomized to either standard CPT or modified CPT that included cognitive rehabilitation strategies (SMART-CPT). Those who dropped out of treatment prematurely performed more poorly on EF tests at baseline than treatment completers. Worse baseline performances on EF tests of working memory, inhibition, and inhibition/switching were associated with poorer response to CPT (less reduction in PTSD symptoms). In addition, a three-way interaction indicated that individuals with worse baseline cognitive flexibility did not benefit as much from standard CPT but demonstrated significant PTSD symptom improvement in the SMART-CPT condition, comparable to those with better baseline cognitive flexibility. Modifying CPT to accommodate executive dysfunction may boost treatment effectiveness and allow Veterans to fully engage in and benefit more from components of CPT (e.g., cognitive restructuring). Highlights: Individuals who dropped out of PTSD treatment had worse baseline executive function. Worse baseline executive function was associated with reduced treatment response. Those with worse cognitive flexibility didn't benefit as much from standard therapy. Adding cognitive rehabilitation strategies to standard treatment improved outcomes.